2008
DOI: 10.1002/pon.1437
|View full text |Cite
|
Sign up to set email alerts
|

Fear of recurrence in long‐term testicular cancer survivors

Abstract: High levels of FoR in long-term TCSs are not uncommon. Levels of mental and somatic problems are associated with the levels of FoR. Clinical consequences of these findings for TCSs are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
200
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(219 citation statements)
references
References 40 publications
11
200
2
6
Order By: Relevance
“…Multivariate analysis using these data showed a small, significant association between not being in paid work and approach coping; there was no significant association between education and coping strategy [34]. Using data from the same study of Norwegian survivors, Skaali et al found that unemployment, men with 12 or fewer years of education, and economic problems were significantly associated with fear of recurrence [32].…”
Section: Sep and Survivorshipmentioning
confidence: 94%
See 1 more Smart Citation
“…Multivariate analysis using these data showed a small, significant association between not being in paid work and approach coping; there was no significant association between education and coping strategy [34]. Using data from the same study of Norwegian survivors, Skaali et al found that unemployment, men with 12 or fewer years of education, and economic problems were significantly associated with fear of recurrence [32].…”
Section: Sep and Survivorshipmentioning
confidence: 94%
“…This makes infertility an issue for TC survivors [78,83], but we found no studies that described the association of infertility and SEP. Distress about loss of fertility as a psychosocial outcome is addressed by 1 of the articles in our review. For this review, we identified 8 articles that examined how psychosocial outcomes are influenced by SEP in TC survivors [29][30][31][32][33][34][35][36]. The relationship between psychological outcomes and SEP was not consistent in TC survivors.…”
Section: Sep and Survivorshipmentioning
confidence: 99%
“…Mini-Mac analysis showed significantly correlations among cancer pain for hopelessness and anxious preoccupation coping styles (p<0.05). These patients, when confronted with a painful situation, were characterized by negative selfstatements, negative thoughts about future and exhibited greater level of cancer worries and higher level of perceived risk of recurrence of pain than the other group [33]. In studies of subjects with cancer pain, catastrophizing has been linked to increased pain intensity, anxiety and depression [34].…”
Section: Discussionmentioning
confidence: 99%
“…Las variables asociadas con la presencia de ansiedad son: edad joven, neuropatía periférica, desempleo, problemas económicos, riesgo de infertilidad, disfunción sexual, consumo excesivo de alcohol y drogas, miedo a la recaída y haber sido tratados por problemas mentales previamente (8,33,34) . La mayoría de los sobrevivientes de cáncer testicular informaron la presencia de miedo a la recurrencia del cáncer, siendo propensos a atribuir cualquier tipo de síntoma o malestar físico a la posibilidad de recurrencia de la enfermedad (7,17,22) .…”
Section: Ansiedadunclassified
“…Diversos estudios han identificado la problemática psicológica que cursan los pacientes con cáncer, principalmente trastornos de ansiedad y depresión, presentes durante el proceso de atención a su salud (3)(4) . El diagnóstico, tratamiento y periodo de seguimiento tienen repercusiones psicoló-gicas en el paciente con CT, entre las más prevalentes la depresión y la ansiedad (5)(6)(7)(8) . La presencia de ansiedad y depresión en el paciente con CT se encuentran asociadas con la edad joven, la nuliparidad, la neuropatía periférica, el desempleo, los problemas económicos, problemas por el consumo excesivo de alcohol, problemas sexuales y haber sido tratados por problemas de salud mental previamente (9)(10) .…”
Section: Introductionunclassified